Educators’ Attitudinal Shift toward Effective Differentiated Learning Practices: A Transformational Perspective - Angelia, Inge; Raid, Naufal; Isnaini, Isnaini; BP, Silvia Anggreni (The Future of Education Journal, 2025)
The concept of education in the Merdeka Curriculum, based on the philosophy of K.H. Dewantara, emphasizes that all inherent potentials in children should be nurtured to achieve the highest safety and happiness as human beings. Education must accommodate all the diverse needs of children through a learning process known as differentiated instruction. The research problem addressed in this article is the attitude of educators towards differentiated instruction. Therefore, the aim of this article is to explore educators' attitudes regarding differentiated instruction. The research method employed includes in-depth interviews with educators from various backgrounds and direct observations in the classroom, involving 26 teacher respondents. Data analysis was conducted using Miles and Huberman's techniques, which include: Data Reduction, Data Display, and Conclusion/Verification. Data validity was ensured through Source Triangulation. The research findings indicate that a transformation in attitude occurs through educators' deep understanding of the diverse learning needs of children, acceptance of differences, and the ability to adapt to teaching strategies. Survey results reveal that 46% of respondents do not yet understand students' learning styles, 57.1% do not comprehend the interests of students they teach, and 78.6% of educators do not understand students' readiness to learn. Based on these findings, it can be concluded that many teachers have not yet implemented differentiated instruction and believe that uniform teaching methods are more effective than differentiated instruction.The implications of this study suggest the need for ongoing support for educators' professional development and systematic training related to changes in curriculum paradigms. In conclusion, transforming educators' attitudes is a crucial foundation for creating a learning environment that significantly supports the advancement of all students.